Bio-objects: new conjugations of the living - Tamminen, Sakari; Vermeulen, Niki (Sociologias, 2019)
Rapid advances in the life sciences have led to a radical transformation in thinking about what life is: we now compose living beings as synthetic life, from the ground up. “Life” has been multiplied and fragmented in molecular and database form and can be embodied in anything from engineered organisms through organs grown outside the body to bioprinted materials. Such new forms of life disrupt social relationships, challenge boundaries between culturally defined categories, pose new questions for governance, and reshape relations between living and ethics. Building on their earlier work with “bio‑objects”, the authors suggest that this concept can aid greatly in mapping out and analysing the empirical spheres in which new conjugations of life are being re‑articulated. The paper contextualises the concept further via an examination of literature about life, and it systematically identifies key epistemic platforms through which bio-objects are brought to life today.